Distance between the descending aorta and the left inferior pulmonary vein as a determinant of biophysical parameters during paroxysmal atrial fibrillation cryoablation. (8th September 2021) - Benali, Karim; Da Costa, Antoine; Macle, Laurent; Hammache, Nefissa; Galand, Vincent; Romeyer, Cécile; Guichard, Jean Baptiste; Leclercq, Christophe; Pavin, Dominique; Martins, Raphaël
Abstract: Introduction: The distance from the descending aorta (DA) to the posterior wall of the left atrium (LA) is variable. We aimed to determine whether the proximity between the DA and the left inferior pulmonary vein (LIPV) ostium has an impact on biophysical parameters and cryoballoon (CB) ablation efficacy during LIPV freezing. Methods: Patients referred for CB‐ablation of atrial fibrillation (AF) in two high‐volume centers were included. Cryoablation data were collected prospectively for each patient. The anatomical relationships between the LIPV and the DA (distance LIPV ostium‐DA, presence of an aortic imprint on the posterior aspect of the LIPV) were then retrospectively analysed on the LA computed tomography scans realized before AF ablation. Results: A total of 350 patients were included (70% men, 59.7 ± 11.5 years). The decrease in the Ostium‐DA distance was significantly correlated to the increase in the time‐to‐isolation (TTI) ( r = −.31; p = .036), with less negative temperature ( r = −.11; p = .045). Similarly, the presence of an aortic imprint on the LIPV was associated with a longer TTI ( p < .001). The analysis of redo procedures data shows a trend toward the presence of shorter ostium‐DA distances (15.3 ± 3.29 vs. 18.1 ± 4.99, p = .15) and more frequent aortic imprints (63.6% vs. 47.5%, p = .34) in patients with LIPV reconnection as opposed to patients without reconnection in the LIPV. Conclusion: Our findings indicated that the DA seems to have a "radiator" effect influencing LIPV cryoablation parameters during CB‐ablation. Additional studies will be needed to elucidate whether this biophysical influence has a clinical impact in LIPVs reconnections. Graphical abstract: